Conventional vs Microwave assisted SiO2/P2O5 catalyzed synthesis of Schiff bases. (March 2020) - Mishra, N; Yadav, R; Kumar, K; Pandey, H; Pandey, R
Abstract: Here in this work we have carried out synthesis of isoniazid and their benzaldehyde derivative in the presence of SiO2 /P2 O5 catalyzed utilizing conventional and microwave assisted protocols. Both these protocols examined comparatively and we found that microwave assisted synthesis is more efficient, eco-friendly and economical method as compared to conventional method. Yield of product is also higher than conventional method. Use of heterogeneous catalyst is also promoting the yield of product and it is very easy to separate from the product by simple filtration and centrifugation. These synthesized compounds are characterized by physical and spectral studies (IR, UV-VIS, NMR spectroscopy) Isoniazid having excellent antitubercular activity and due to presence of Isoniazid they may have good antibiotic property.